Knowledge discovery in research on policing strategies: an overview of the past fifty years - Basilio, Marcio Pereira; Pereira, Valdecy; Oliveira, Max William Coelho Moreira de (Journal of modelling in management, 2022)
Purpose The insecurity generated, today in various parts of the planet, by the various conflicts that arise in the violence in large cities, has motivated the academy to research the solutions and strategies adopted by local governments in the fight against crime. The volume of data generated by several universities over the past 50 years has increased exponentially. Consequently, researchers struggle to process essential data in today’s competitive world. The aim of this study is to explore and provide an overview of the studies carried out in the field of action to combat crime in different countries. Design/methodology/approach The Web of Science and Scopus databases were searched for publications from January 1945 to September 3, 2020 on the topic of policing strategies in titles, abstracts and keywords. References were analyzed using the R bibliometrix package, and abstracts were analyzed using latent Dirichlet allocation (LDA) with collapsed Gibbs sampling for topics related to policing and related subjects. Findings As a result of the research, this paper can assert that in the last 50 years, 3,361 authors have produced 2,085 documents on the theme of policing strategy and related subjects in 58 countries. Scientific production in this area grows at a rate of 5.10 per year. The USA is the leading country in publications with 42.58%, followed by the UK with 8.39% and Canada with 4.07%. As for journals, the highlight is Policing, Policing and Society and Police Quarterly, which account for more than 15.44% of all indexed literature. Regarding the authors, the highlight is Weisburd and Braga. As a result, the LDA grouped the latent words in the articles analyzed by themes studied and presented the list of articles by themes. The thematic map identifies the following themes as basic research subjects: community policing, problem-oriented policing, predictive policing, fear of crime and social control. Practical implications As the main implication between the combination of the bibliometric analysis method with the probabilistic topic modelling, is the emergence of a primordial step in the systematic literature review process, as this method allows to explore and group a large volume of data. Another practical implication that is intended is to provide the beginning researcher or any other reader with a panoramic view of the main authors who study the themes that impact police activity in any city in the world, which are the countries and reference centers of the study on the subject and, finally, the evolution of the main themes researched in the police area. Originality/value The value of these studies is summarized in the presentation of an overview on the theme in the last 50 years, offering the opportunity for other researchers to use this research as a starting point for other analyses.